Frontiers in the economics of crime: Lessons for Latin America and the Caribbean - Laura Jaitman (Latin American Economic Review, 2019)
Crime and violence generate many distortions in the allocation of private and public resources and engender economic and social costs that hinder development. In Latin America and the Caribbean, which is the most violent region on earth, the costs of crime represent at least 3.5% of the regional gross domestic product, twice as much as in developed countries. Despite the magnitude of the security problem, the region is lagging in the production of rigorous research on crime and the application of evidence-based policies to fight and deter crime. This paper uses the crime economics framework to shed light on the main drivers of crime and proposes avenues for future research and action in the region to reduce crime and its social and economic costs.
Keywords: K00; K42; O10; O17; O54; Z18; 330; Crime; Costs of crime; Crime policies; Latin America and the Caribbean